Shipwrecks and underwater objects of the southern Baltic – Hard substrata islands in the brackish, soft bottom marine environment. (30th September 2019) - Balazy, Piotr; Copeland, Ula; Sokołowski, Adam
Abstract: Objects of anthropogenic origin submerged in the sea, such as shipwrecks, may induce significant environmental changes in their close proximity. There may be more than 100 000 shipwrecks in the Baltic Sea, however to date, their effects on biodiversity by the introduction of large hard substrates in this typically low-evenness, species-poor ecosystem have received little attention. This study compared separately macrobenthic assemblages found on three different objects (an old torpedo house, a former submarine and a minesweeper) lying at various depths (2–21 m) in Puck Bay (the Gulf of Gdańsk, Baltic Sea), and corresponding assemblages in soft sediments from their close (5 m away) and far vicinity (50 m away). A total of 26 taxa of macrobenthic algae, vascular plants and fauna were recorded. Nineteen species were found directly on the study objects. Nine species among them were only found on the submerged objects but none was substrate specific. At two locations clear differences in the assemblage structure between seabed in the close proximity of submerged objects and the seabed located farther apart were noted. Higher species richness, abundance and diversity (measured as Shannon-Wiener H′ ) was recorded only in the location of the deepest object. Its high similarity (both in terms of the assemblage structure and S, N, H' ) with the closest neighbouring sediments may indicate a direct impact of the object on the surrounding seabed. The submerged objects generally supported a two - three times higher number of species and a ∼25 times higher number of individuals (but not diversity) than the soft bottom in the vicinity. The shallowest object lying within the euphotic zone hosted the most species rich (on avg. 10 species/144 cm 2 ) and abundant (on avg. 379 ind./144 cm 2 ) assemblages. Differences in the assemblage structure found between different objects are most likely associated with depth related environmental variables. The results of the study can serve as a baseline for future investigations and for evaluation of local ecological effects of the artificial reef concepts, breakwaters and offshore wind farms. Graphical abstract: Image 1 Highlights: Assemblages in proximity of objects are different from those located farther away. Increased S N H′ in proximity of objects was recorded only on the deepest location. Wrecks may impact the surrounding soft bottom at least to the 5 m distance. Depth related variables contribute also to differences in macrofauna among wrecks. More diverse and numerous assemblages occupy shallower wrecks.